Aromatic polyimides from m-phenylene diamines containing pendant groups: synthesis and characterization - Pal, R. R.; Patil, P. S.; Dere, R. T.; Salunkhe, M. M.; Maldar, Noormahamad N.; Wadgaonkar, P. P. (Journal Applied Polymer Science, 2005)
Two diamine monomers, 4-[4-(1-methyl-1-phenyl)phenoxy]-1,3-(diamino benzene and 4-{-[(4-methylphenyl)sulfonyl]phenoxy}-1,3-diamino benzene, were synthesized, and both diamines were polycondensed with three commercial dianhydrides to obtain aromatic polyimides containing pendant groups. The polyimides were characterized by solubility tests, viscosity measurements, IR, H-1-NMR, and C-13- NMR spectroscopy, x-ray diffraction studies, and thermogravimetric analysis. The polymides had inherent viscosities of 0.33-0.58 dL/g in m-cresol at 30 +/- 0.1 degrees C. All the polyimides were amorphous and were soluble in solvents such as NNdimethylacetamide, N-methyl-2-pyrrolidone, N,N-dimethylformamide, and in-cresol. Thermogravimetric analysis of the polymides indicated no weight loss below 410 degrees C under a nitrogen atmosphere. (c) 2005 Wiley Periodicals, Inc.
Keywords: heteroatom-containing polymers; High performance polymers; polyimides

Hydrophobically modified poly(acrylic acid) using 3-pentadecylcyclohexylamine: synthesis and rheology - Shedge, A. S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique; Pcrrin, P.; Chassenieux, Christophe; Badiger, Manohar V. (Macromolecular Chemistry and Physics, 2005)
Hydrophobically modified poly(acrylic acid) was synthesized using 3-pentadecylcyclohexylamine (3-PDCA), which was in turn synthesized from 3-pentadecylphenol, one of the components of cashew-nut shell liquid (CNSL), a renewable resource material. H-1 NMR spectra confirmed the incorporation of 3-PDCA onto PAA and a series of HMPs with three different molar concentrations, viz. congruent to 3, 5 and 7 mol-% of 3-PDCA, were synthesized. An increase in viscosity with increasing hydrophobic content was observed by rheological measurements. The critical association concentrations were determined using an Ubbelohde viscometer and a controlled stress rheometer. The stability of HMPs towards temperature and shear was studied. Rheological measurements showed that there was a steady increase in viscosity with increase in hydrophobe content due to the formation of reversible networks. These polymers exhibited gel-like behavior at low concentrations (greater than or equal to2 wt.-%) with an apparent yield stress (ca. 10 Pa) and showed shear thinning properties (non-Newtonian). However, below a critical concentration, c [eta], they showed Newtonian behavior.
Keywords: 3-pentadecylcyclohexylamine (3-PDCA); hydrophobically modified polymers (HMPs); poly(acrylic acid); reversible associations; Rheology

Synthesis and characterization of aromatic polyamides containing an s-triazine ring with thiophenoxy linkages - Pal, R. R.; Patil, P. S.; Salunkhe, M. M.; Maldar, Noormahamad N.; Wadgaonkar, P. P. (Polymer International, 2005)
A series of aromatic polyamides containing an s-triazine ring with thiophenoxy linkages was synthesized from two new diacids, namely 2,4-bis-(4-carboxyphenoxy)-6-thiophenoxy-s-triazine and 2,4-bis-(3-carboxyphenoxy)-6-thiophenoxy-s-triazine, and commercially available aromatic diamines by using Yamazaki's phosphorylation reaction. The polyamides were obtained in good yields and were characterized by solubility tests, viscosity measurements, FTIR, H-1 and C-13 NMR spectroscopy, X-ray diffraction studies and thermogravimetric analysis. The polyamides were found to have inherent viscosities in the range of 0.35 to 0.56 dl g(-1) in N,N-dimethylacetamide (DMAc) at 30 +/- 0.1 degreesC. All the polyamides were readily soluble in solvents such as DMAc, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF) and m-cresol. Thermogravimetric analysis of the polyamides indicated no weight loss below 345 degreesC under a nitrogen atmosphere. (C) 2004 Society of Chemical Industry.
Keywords: 2; 4-bis-(3/4-carboxyphenoxy)-6-thiophenoxy-s-triazine; direct polycondensation; polyamide; s-triazine ring

Synthesis, structure, electrochemistry and ROMP-activity of new ferrocenyl analog of Grubbs' metathesis catalyst - Maishal, T. K.; Mondal, Biplab; Puranik, Vedavati G.; Wadgaonkar, P. P.; Lahiri, Goutam Kumar; Sarkar, A. (Journal of Organometallic Chemistry, 2005)
Treatment of [(PCy3)(2)Cl2Ru=CH-Ph] (1) with vinylferrocene 1 and 1-ferrocenyl-1,3-butadiene 2 yielded solid products. These new complexes were characterized by H-1 NMR, P-31 NMR and C-13 NMR spectroscopy. X-ray crystal structures of both the complexes have been solved. The crystal structure of II confirmed the assigned structure and revealed existence of two sets of intermolecular C-H-Cl(M) type interactions, viz. (Ru)Cl-H-C(ferrocene) and (Ru)Cl-H-CHCl2. The air-stable, dark solid II is all efficient catalyst for ring-opening metathesis polymerization (ROMP) of cyclopentene, norbornene and cycloocta-1,5-diene. Electrochemical behavior of the complexes clearly reflects electronic communication between two metal centers. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Electrochemistry; ferrocene; Metathesis; non-covalent interactions; ring-opening metathesis polymerization; ruthenium carbene

Thermoreversible behavior of associating polymer solutions: thermothinning versus thermothickening - Hourdet, Dominique; Gadgil, Jayant; Podhajecka, K.; Badiger, Manohar V.; Brulet, A.; Wadgaonkar, P. P. (Macromolecules, 2005)
Self-assembling properties of poly(sodium acrylate) grafted with dodecyl [C12], PAAgC12, or poly(N-isopropylacrylamide) [PNIPA] side chains, PAAgPNIPA, were studied in unentangled semidilute aqueous solution. While PAAgC12 self-associates through hydrophobic interactions, the gelation of PAAgPNIPA is triggered by heating in response to the lower critical solution temperature of PNIPA (LCST similar to 32 degrees C). The local structure of the physical networks was investigated by small-angle neutron scattering, and the scattering patterns were described using a polydisperse sphere model taking into account hard-sphere interactions. This model allow us to draw a realistic picture of physical gels with quantitative information concerning the size of hydrophobic cores, the volume fraction of stickers in the aggregates, the fraction of stickers which take part in the aggregation process, the range of repulsive interactions, and the structural modifications induced by temperature. The description of the network is in good agreement with complementary data obtained from DSC and C-13 NMR. In the present work, a special emphasis has been given to the important relationship existing between the viscoelastic properties of associating polymer solutions and the binding energy of stickers leaving temporarily the micellar junction. Depending on the endothermic or exothermic nature of the disengagement process of the sticker (heat of demicellization), the relaxation time of the network and the viscoelastic properties will either decrease or increase with the temperature. The consequence is that aqueous solutions of PAAgC12 and PAAgPNIPA exhibit opposite rheological properties with the temperature, namely thermothinning and thermothickening. By mixing these two copolymers, we show that intermediate properties can be obtained but in that case a microphase-separated network is obtained as a result of copolymer segregation.

Chemoselective dithioacetalization of aldehydes using silica sulfuric acid as a reusable catalyst - Pore, D. M.; Desai, Uday V.; Mane, R. B.; Wadgaonkar, P. P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2006)
Silica sulfuric acid has been found to be an efficient and reusable catalyst for chemoselective dithioacetalization of aldehydes over ketones, in excellent yields.
Keywords: Chemoselective; dithioacetalization; silica sulfuric acid

Efficient deprotection of dithioacetals to carbonyls using Oxone-KBr in aqueous acetonitrile - Desai, Uday V.; Pore, D. M.; Tamhankar, B. V.; Jadhav, Sushilkumar A.; Wadgaonkar, P. P. (Tetrahedron Letters, 2006)
A simple and efficient method has been developed for the chemoselective dethioacetalization of dithioacetals to aldehydes and ketones using Oxone-KBr in aqueous acetonitrile at room temperature. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: deprotection; dethioacetalization; Oxone

Efficient, solvent-free method for the chemoselective synthesis of acylals from aldehydes and their deprotection catalyzed by silica sulfuric acid as a reusable solid acid catalyst - Desai, Uday V.; Thopate, T. S.; Pore, D. M.; Wadgaonkar, P. P. (Catalysis Communications, 2006)
An efficient method has been developed for the chemoselective synthesis of acylals from aldehydes and acetic anhydride in the presence of silica sulfuric acid as a reusable solid acid catalyst under solvent-free conditions. Ketones are found to remain unaffected under the reaction conditions. The deprotection of acylals has also been achieved using SSA in methanol medium. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylals; aldehydes; Chemoselective; protection and deprotection silica sulfuric acid

Synthesis and characterization of novel hydrophobically end-capped poly(ethylene oxide)s [PEOs] - Badiger, Manohar V.; Kadam, Vijay S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique (Macromolecular Symposia, 2006)
We report on the synthesis and characterization of a novel hydrophobically modified end-capped poly(ethylene oxide)s. The end-capping agent of this polymer was designed and synthesised from a renewable resource material namely, gallic acid (i.e. 3,4,5-trihydroxybenzoic acid), the byproduct of tannin industry. The hydroxyl groups at 3, 4 and 5 positions of gallic acid provide an opportunity for varying the hydrophobicity of the compound. The hydrophobic end-capping compound, 3,4,5tridodecyloxy bezoylazide was prepared from gallic acid and PEGS with different chain lengths (of number average molecular weights, 10000 and 35000 g/mol) were endcapped. using 3,4,5-tridodecyloxybenzoyl azide. The quantitative analysis of end-capping in the polymers was demonstrated by H-1-NMR spectroscopy and the rheological studies were carried out in the surfactant solutions.
Keywords: end-capped PEOs; hydrophobically modified polymers; water-soluble polymers

Anhydrous magnesium sulfate mediated solvent-free synthesis of dihydropyrimidin-2(1H)-ones at ambient temperature - Pore, D. M.; Desai, Uday V.; Thopate, T. S.; Wadgaonkar, P. P. (Australian Journal of Chemistry, 2007)
An anhydrous magnesium sulfate mediated solvent-free protocol is described for the synthesis of dihydropyrimidinones (Biginelli compounds) at ambient temperature.

Rapid extraction and separation of indium(III) with a high molecular weight amine - Shilmkar, T. N.; Kolekar, S. S.; Wadgaonkar, P. P.; Anuse, Mansing A. (Indian Journal of Chemical Technology, 2008)
The liquid-liquid extraction of indium(III) from sodium succinate media using n-octylaniline in toluene as an extractant was studied. Quantitative extraction of indium(III) was observed in the range of 0.004-0.0075 M sodium succinate at pH 3.8-6.0 with 4% n-octylaniline in toluene. Indium(III) was completely stripped from the metal loaded organic phase of the extractant with water and determined complexometrically. The stoichiometry of the extracted species was determined on the basis of;slope analysis. The extraction was found to proceed by a ion-pair mechanism with the extracted species being [RNH3+In(succinate)(2)(-)](org). Separation of indium(III) was carried out from some associated metals like Tl(I), Mg(II), Ni(II), Cu(II), Zn(II),. Cd(II), Hg(II), Pb(II), GC(IV), Sb(III), Bi(III). The selectivity of the extraction of indium(III) can also be achieved by use of a suitable masking agent for estimation and determination from the synthetic mixture corresponding to alloy to show the practical utility of the extractant.
Keywords: Indium(III); n-octylaniline; Separation; solvent extraction; succinate

Sulfamic acid: an efficient and cost-effective solid acid catalyst for the synthesis of alpha-aminophosphonates at ambient temperature - Mitragotri, Satish D.; Pore, D. M.; Desai, Uday V.; Wadgaonkar, P. P. (Catalysis Communications, 2008)
Sulfamic acid catalyzed solvent-free protocol has been developed for the synthesis of alpha-aminophosphonates by three component condensation between aldehydes, amines and diethyl phosphite at ambient temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aminophosphonates; diethylphosphite (DEP); solid acid catalyst; Solvent-free; sulfamic acid (SA)

Composites of plasma treated poly(etherimide) films with gold nanoparticles and lysine through layer by layer assembly: a ``friendly-rough'' surface for cell adhesion and proliferation for tissue engineering applications - D'Britto, Virginia; Tiwari, S.; Purohit, V.; Wadgaonkar, P. P.; Bhoraskar, S. V.; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2009)
A composite film fabricated by plasma treated poly(etherimide) with subsequent deposition of gold nanoparticles and lysine using layer by layer assembly has been demonstrated to be good for cell attachment and proliferation making it an attractive strategy for tissue engineering applications. As compared to the other methods the decrease in contact angle obtained here does not depend much on the plasma treatment thus affecting the polymer structure minimally. A combination of surface roughness provided by the gold nanoparticles and the presence of amine groups of lysine is hypothesized to be the reason for the features observed.

Solvent extraction of trivalent indium from succinate solution by 2-octylaminopyridine in chloroform - Mahamuni, Sandip V.; Kolekar, S. S.; Wadgaonkar, P. P.; Anuse, Mansing A. (Journal of the Iranian Chemical Society, 2009)
Extraction processes of indium(III) with 2-octylaminopyridine (2-OAP) from media of various complexing ability, succinate and salicylate, in chloroform have been elucidated. The ion-pair complex has also quantitative extraction in xylene and 1,2-dichloroethane. Indium(III) from organic phase was stripped with 1.0 M hydrochloric acid and determined complexometrically with EDTA. The stoichiometry of the extracted species was found out on the basis of slope analysis. The extraction of indium(III) proceeds by an anion exchange mechanism and the extracted species is [RR'NH(2)(+)In(succinate)(2)(-)]((org)). Temperature dependence of the extraction equilibrium constant was also examined to estimate the apparent thermodynamic functions (Delta H, Delta G and Delta S) for extraction reaction. It is possible to separate indium(III) from Zn(II), Cd(II), Pb(II), Hg(II), Bi(III), Tl(I), Tl(III), Ga(III), Al(III), Te(IV), Se(IV), Sb(III), Fe(III) and Sn(IV). The method is simple, rapid and reproducible and can be used to determine the indium from samples like alloys.
Keywords: 2-OAP; Binary separations; Indium(III); liquid-liquid extraction; Sodium succinate

Synthesis and properties of new polybenzoxazines containing (substituted) cyclohexyl moieties - Kumar, K. S. Santhosh; Nair, C. P. Reghunadhan; Ninan, K. N.; Kulkarni, A. D.; Wadgaonkar, P. P. (Polymers for Advanced Technologies, 2009)
A series of new polybenzoxazines were synthesized based on diphenols containing (substituted) cyclohexyl moiety and were characterized by FT-IR, (1)H-NMR, and (13)C-NMR spectroscopy. These new benzoxazine monomers exhibited better processability with lower peak cure temperature and a wide cure controllable window (CCW) as manifested in differential scanning calorimetric analysis. The cure analysis was performed by FT-IR spectroscopy. Glass transition temperature of new polybenzoxazines varied from 170 to 205 degrees C. The cyclohexyl bridge groups facilitated ring opening, resulting in polymer with improved thermal stability in comparison to bisphenol A-based benzoxazine as assessed by the various thermal analyses. The water contact angles of polybenzoxazines containing (substituted) cyclohexyl moieties were higher than that of bisphenol A-based polybenzoxazine, implying their higher hydrophobicity. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: Hydrophobicity; polybenzoxazines; thermally stable polymers

Synthesis and thermal properties of soluble silicon containing phenylated aromatic-aliphatic polyamides - Ghanwat, A. A.; Sayyed, M. M.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Journal of Thermal Analysis and Calorimetry, 2009)
Aromatic polyamides find many applications in diverse and critical areas due to their high thermal stability coupled with high mechanical properties. However most of such aramides are difficult to fabricate because of their limited solubility and high melting temperature. Improvements in processability have been reported by incorporating bulky pendant groups and aliphatic spacer groups. Similarly to improve the solubility of polymers approaches of incorporating silicon in main polymer chain and co-polymerization techniques were useful. We report the synthesis and characterization of a series of phenylated silicon containing aromatic-aliphatic polyamides from a mixture of 2, 5-bis (4-carboxy methylene phenyl)-3, 4-diphenyl thiophene (CMPDT) and bis-(4-carboxy phenyl) dimethyl silane (BCPDS) in various mole proportions, with commercial aromatic diamine. Thus a series of novel co-polyamides having pendant phenyl groups, methylene spacer and silicon moiety was prepared by judicious combination of (CMPDT); BCPDS and aromatic diamine; bis-(4-aminophenyl) ether (ODA), by direct polycondensation using Yamazaki's phosphorylation method. These high molecular mass polyamides were obtained in high (89-98%) yields and had viscosities in the range of 0.23-0.57 dL/g in DMAc. Polyamides showed improved solubility in polar aprotic solvents, like NMP, DMAc, DMSO and DMF; had high thermal stability; with no mass loss below 335 A degrees C.
Keywords: 2; 4-diphenyl thiophene; 5-bis (4-carboxy methylene phenyl)-3; bis-(4-amino phenyl) ether; bis-(4-carboxy phenyl) dimethyl silane; Copolyamides; solubility; thermal stability

Novel poly(amide-hydrazide)s and copoly(amide-hydrazide)s from Bis-(4-aminobenzyl) hydrazide and aromatic diacid chlorides: synthesis and characterization - Medhi, M.; Patil, A. S.; Halhalli, Mahadeo R.; Choubey, A.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Journal of Applied Polymer Science, 2010)
A new aromatic diamine, viz., bis-(4-aminobenzyl) hydrazide (BABH), which contains preformed hydrazide and methylene linkage, was synthesized starting from alpha-tolunitrile. The BABH and intermediates involved in its synthesis were characterized by spectroscopic methods. Novel poly(amide-hydrazide)s were synthesized by low temperature solution polycondensation of BABH with isophthaloyl chloride (IPC) and terephthaloyl chloride (TPC). Furthermore, two series of copoly(amide-hydrazide)s, based on different mol % of BABH and bis-(4-aminophenyl) ether (ODA) with IPC/TPC were also synthesized. Poly(amidehydrazide)s and copoly(amide-hydrazide)s were characterized by inherent viscosity [eta(inh)], FTIR, solubility, X-ray diffraction (MUD), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The polycondensation proceeded smoothy and afforded the polymers with inherent viscosities in the range of 0.18-093 dL/g in (NMP + 4% LiCl) at 30 degrees C +/- 0.1 degrees C. These polymers dissolved in DMAc, NMP or DMSO containing LiCl. The solubility of copolymers was considerably improved in line with less crystalline nature due to random placement of constituent monomers during the copolymerization. XRD data indicated that poly(amide-hydrazide)s from BABH alone and IPC/TPC had higher crystallinity than the corresponding copoly(amide-hydrazide)s derived from a mixture of BABH and bis-(4-aminophenyl) ether (ODA). Polymers showed initial weight loss around 160 degrees C which is attributed to the cyclodehydration leading to the formation of corresponding poly(amide-oxadiazole)s. Copolyamide-hydrazides showed, T(max) between 400 and 540 degrees C which is essentially the decomposition of poly(amide-oxadiazole)s. (C) 2010 Wiley Periodicals, Inc. J App Polym Sci 116: 2441-2450, 2010
Keywords: bis-(4-aminobenzyl) hydrazide; poly(amide-hydrazide); structure-property relations; Thermogravimetric analysis (TGA); x-ray diffractograms

Synthesis and characterization of novel aromatic-aliphatic polyamides from bis-[(4-aminobenzyl)-4-benzamide] ether - Patil, A. S.; Medhi, M.; Sadavarte, Nilakshi V.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A novel aromatic diamine monomer containing preformed aromatic-aliphatic amide and ether linkage, bis-[(4-aminobenzyl)-4-benzamide] ether (BABE) was prepared from 2-phenylacetonitrile. BABE was characterized by FT-IR, (1)H NMR, (13)C NMR and mass spectrometry. Five new aromatic polyamides were prepared by low temperature solution polymerization from BABE and different mole proportions of isophthaloyl chloride (IPC) or terephthaloyl chloride (TPC). The resulting polymers were characterized by means of FT-IR, inherent viscosity [eta(inh)], solubility, differential scanning calorimetry [DSC], thermogravimetric analysis [TGA] and X-ray diffraction [XRD]. Polyamides were obtained in good yields and had moderate to high molecular weights as indicated by inherent viscosities in the range 0.63-1.35 dL/g in (DMAc + 4% LiCl). XRD results showed the partly crystalline nature of polymers and these polymers dissolved in aprotic polar solvents containing LiCl. The solubility of copolyamides improved due to random placement of constituent IPC and TPC during polymerization. DSC analysis of these polyamides showed glass transition temperatures in the range of 197-204 degrees C, and they showed no weight loss below 336 degrees C when analyzed by TG. These polyamides have potential applications as engineering materials. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bis-[(4-aminobenzyl)-4-benzamide] ether; ether linkage; Inherent viscosity; polyamides; thermal stability; XRD

Synthesis and characterization of polyesters from 2,3-bis (4 `-hydroxy phenyl) quinoxaline and 2,3-bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline - Patil, V. B.; Medhi, M.; Bhairamadgi, Nagendra S.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
Two bisphenols containing pendant, quinoxaline moiety; 2,3-bis (4'-hydroxy phenyl) quinoxaline (BHPQ) and 2,3-bis (2'-hydroxynaphthalene-6-yl) quinoxaline (BHNQ) were synthesized and characterized by FT-IR, (1)H, (13)C NMR and mass spectrometry. Aromatic polyesters and copolyesters were prepared by interfacial polymerization from BHPQ or BHNQ and isophthaloyl chloride or terephthaloyl chloride or a mixture of different mole proportions of (IPC + TPC). These polyesters and copolyesters were characterized by spectroscopic technique, viscosity measurement, solubility, thermal stability. DSC and XRD. Polymers had moderate to high molecular weights as evidenced by the inherent viscosities in the range 0.35-0.78 dL/g for BHPQ series and 0.27-0.52 dL/g for BHNQ series. BHPQ polyesters and copolyesters dissolved in m-cresol, NMP and conc. H(2)SO(4) whereas, BHNQ polyesters and copolyesters were readily soluble in NMP, DMAc, (TCE + phenol) and partly soluble in solvent like CHCl(3), pyridine, etc. Wide angle X-ray diffraction (WAXD) results showed that introduction of quinoxaline moiety into polymer chain and aromatic phenyl/rigid naphthyl structures lead to crystalinity. Differentional scanning calorimetry of BHNQ polyesters showed the glass transition temperatures in the range of 131-151 degrees C. BHPQ polyesters did not show any weight loss below 330 degrees C and retained 27-55% weight at 900 degrees C when investigated by TGA under nitrogen atmosphere demonstrating good thermal stability BHNQderived polyesters showed initial decomposition temperatures in range 211-234 degrees C. The structure-property relationships for the mentioned polyesters are analyzed, as these polyesters are of interest as materials for electronics, microelectronics and membrane separation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 2; 3-Bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline; 3-Bis (4 `-hydroxy phenyl) quinoxaline; Aromatic polyesters; Glass transition temperature; solubility; Thermal properties

Lithium tetrafluoroborate catalyzed highly efficient inter- and intramolecular aza-Michael addition with aromatic amines - Lad, Uday P.; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2011)
Lithium tetrafluoroborate has been demonstrated for the first time to be an efficient catalyst in intermolecular aza-Michael addition aromatic amines to electron deficient alkenes. Suitability of the same catalyst in intramolecular aza-Michael addition leading 2-aryl-2,3-dihydroquinolin-4(1H) ones has also been described. (C) 2011 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-aryl-2; 3-dihydroquinolin-(4H)-1-ones; Anilines; Lithium tetrafluoroborate; Michael addition

Practical and highly efficient protocol for multicomponent synthesis of beta-phosphonomalononitriles and 2-amino-4H-chromen-4-yl phosphonates using diethylamine as a novel organocatalyst - Kulkarni, M. A.; Pandurangi, V. R.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2012)
Diethylamine has been demonstrated for the first time to be a highly efficient organocatalyst in the solvent-free synthesis of beta-phosphonomalononitriles by a three component condensation of aldehyde, malononitrile and dialkyl phosphite at ambient temperature. The applicability of the same catalyst in the synthesis of diethyl (2-amino-3-cyano-chromene-4-yl) phosphonic acid esters has also been described. (c) 2012 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-amino-4H-chromenes; beta-phosphonomalononitriles; diethylamine; multicomponent reactions; organocatalyst; Phospha-Michael reaction

Catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V.; Khot, S. S.; Lad, U. P.; Desai, U. V.; Wadgaonkar, P. P. (Research on Chemical Intermediates, 2017)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone(A (R))-KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone-KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine-Oxone as an unprecedented catalyst-oxidant combination. [GRAPHICS] .
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides

Crystallisation-enhanced bulk hole mobility in phenothiazine-based organic semiconductors - Shinde, D. B.; Salunke, Jagadish K.; Candeias, Nuno R.; Tinti, Francesca; Gazzano, Massimo; Wadgaonkar, P. P.; Priimagi, Arri; Camaioni, Nadia; Vivo, Paola (Scientific Reports, 2017)
A series of three novel donor-acceptor systems based on C(3)-malononitrile-substituted phenothiazines was synthesised in good overall yields and their thermal, spectroscopic, and electrochemical properties were characterised. The compounds were prepared through a sequence of Ullmann-coupling, Vilsmeier-Haack formylation and Knoevenagel-condensation, followed by Suzuki-coupling reactions for introduction of aryl substitutents at C(7) position of the phenothiazine. The introduction of a donor unit at the C(7) position exhibited a weak impact on the optical and electrochemical characteristics of the compounds and led to amorphous films with bulk hole mobilities in the typical range reported for phenothiazines, despite the higher charge delocalisation as attested by computational studies. In contrast, highly ordered films were formed when using the C(7)-unsubstituted 3-malononitrile phenothiazine, exhibiting an outstanding mobility of 1 x 10(-3) cm(2) V-1 s(-1), the highest reported for this class of compounds. Computational conformational analysis of the new phenothizanes suggested that free rotation of the substitutents at the C(7) position suppresses the ordering of the system, thereby hampering suitable packing of the new materials needed for high charge carrier mobility.

Catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using Oxone as an oxidant (vol 43, pg 6875, 2017) - Kupwade, R. V.; Khot, S. S.; Lad, U. P.; Desai, U. V.; Wadgaonkar, P. P. (Research on Chemical Intermediates, 2018)